Removal of anti-nutritional factors of rapeseed protein isolate (RPI) and toxicity assessment of RPI. Issue 2 (22nd December 2021) - Xiong, Zheng; Fu, Yaoyao; Yao, Jun; Zhang, Nan; He, Rong; Ju, Xingrong; Wang, Zhigao
Abstract : We prepared a detoxified rapeseed protein isolate (RPI) by phytase/ethanol treatment based on alkaline extraction and acidic precipitation. Abstract : We prepared a detoxified rapeseed protein isolate (RPI) by phytase/ethanol treatment based on alkaline extraction and acidic precipitation. Contents of protein, fat, ash, moisture, crude fiber, glucosinolates, phytic acid, and phenolics and color were determined. To evaluate the safety of detoxified RPI, five groups of C57 mice (detoxified RPI [10 and 20 g kg −1 ]; commercial soybean protein isolate (SPI) [10 g kg −1 ]; non-detoxified RPI [10 g kg −1 ]; control) were used in the acute-toxicity test. Bodyweight and pathology parameters were recorded at different time points, followed by macroscopic examination, organ-weight measurement and microstructure examination. After pretreatment of rapeseed meals with phytase (enzyme : substrate ratio, 1 : 5 mg g −1 ) for 1.5 h and two-time ethanol extraction for precipitated protein, the chemical characteristics in RPI were protein (88.26%), fat (0.57%), ash (2.72%), moisture (1.90%), crude fiber (0.77%), glucosinolates (0 μmol g −1 ), phytic acid (0.17%), phenolics (0.36%) and whiteness (73.38). Treatment resulted in significant removal of anti-nutritional factors (ANFs) and increased whiteness in detoxified RPI compared with non-detoxified RPI, and lower than in cruciferin-rich canola protein isolate (Puratein®). Experimental-related effects on bodyweight, clinical observations, or clinicopathology, in mice treated with detoxified RPI were not observed except for a decreased thyroid gland/parathyroid gland index in mice treated with non-detoxified RPI. Furthermore, the no-observed-effect level (NOEL) was 10 g kg −1 of detoxified RPI, whereas the no-observed-adverse-effect-level (NOAEL) was the highest fed level of 20 g kg −1 of detoxified RPI. Overall, detoxified RPI prepared by the combined treatment of phytase and ethanol was considered safe under the conditions tested, in which the contents of the main ANFs were reduced significantly.